Geochemical Responses to Anthropogenic and Natural Influences in Ebinur Lake Sediments of Arid Northwest China - Ma, Long (PLoS One, 2016)
Geochemical concentrations were extracted for a short sediment core from Ebinur Lake, located in arid northwest China, and mathematical methods were used to demonstrate the complex pattern of the geochemical anomalies resulting from the temporal changes in natural and anthropogenic forces on the lake sediments. The first element assemblage (C1) (aluminum, potassium, iron, magnesium, beryllium, etc.) was predominantly terrigenous; among the assemblage, total phosphorus and titanium were generally consistent with aluminum except with regards to their surface sequences, which inferred the differences of source regions for terrigenous detrital material led to this change around ca. 2000AD. The second assemblage (C2) (calcium and strontium) was found to have a negative relationship with aluminum through a cluster analysis. The third assemblage (C3) included sodium and magnesium, which were influenced by the underwater lake environment and deposited in the Ebinur depression. The concentration ratio of C1/(C1+C2) was used as an indicator for denudation amount of detrital materials, which was supported by the values of magnetic susceptibility. The enrichment factors for heavy metals suggested that the influence of human activities on heavy-metal enrichment in Ebinur Lake region was not severe over the past century. Prior to the 1960s, geochemical indicators suggested a stable lacustrine environment with higher water levels. Beginning in the 1960s, high agricultural water demand resulted in rapid declines in lake water level, with subsequent increases of lake water salinity, as evidenced by enhanced sodium concentration in lake core sediments. During this period, anthropogenic activity also enhanced the intensity of weathering and the denudation of the Ebinur watershed.